Functional Pyrimidine‐Based Thermally Activated Delay Fluorescence Emitters: Photophysics, Mechanochromism, and Fabrication of Organic Light‐Emitting Diodes. Issue 12 (31st January 2017) - Ganesan, Paramaguru; Ranganathan, Revathi; Chi, Yun; Liu, Xiao‐Ke; Lee, Chun‐Sing; Liu, Shih‐Hung; Lee, Gene‐Hsiang; Lin, Tzu‐Chieh; Chen, Yi‐Ting; Chou, Pi‐Tai
Abstract: A new series of molecules, T1–T4, possessing thermally activated delayed fluorescence (TADF) have been strategically designed and synthesized. Molecules T1–T4 contain the dimethyl acridine as the electron donor, which is linked to either symmetrical or unsymmetrical diphenyl pyrimidine as an acceptor. In comparison to the ubiquitous triazine acceptor, the selection of pyrimidine as an acceptor has advantages of facile functionalization and less stabilized unoccupied π orbitals, so that the energy gap toward the blue region can be accessed. Together with acridine donors, the resulting donor–acceptor functional materials reveal remarkable TADF properties. In the solid state, molecules T1–T4 all exhibit intriguing mechanochromism. The crystal structures, together with spectroscopy and dynamics acquired upon application of stressing, lead us to propose two types of structural arrangement that give distinct emission properties, one with and the other without TADF. Upon fabricating organic light‐emitting diodes, the T1–T4 films prepared from sublimation all exhibit dominant TADF behavior; this accounts for their high performance: an electroluminescent emission at λ =490 nm, with an external quantum efficiency of 14.2 %, can be attained when T2 is used as an emitter. Abstract : Functional pyrimidine acceptors : A new series of molecules, T1–T4, possessing thermally activated delayed fluorescence (TADF) have been strategically designed and synthesized. Together with acridine donors, the resulting donor– acceptor functional materials reveal remarkable TADF properties. In the solid state, molecules T1–T4 also exhibit intriguing mechanochromism (see figure).